Physical Characteristics on Crumble Ration of Broiler Starter Using Tapioca, Bentonite and Onggok Binders - Y. Retnani; L. Herawati; S. Khusniati (Jurnal Ilmu dan Teknologi Peternakan, 2011)
Quality of ration can be evaluated using several methods, such as chemical, biological and physical test. Physical characteristics of ration are important aspects in feed mill industry, because they are related to handling efficiency, processing and storage. The purpose of this study was to evaluate the influence of using tapioca, bentonite and onggok binders on the physical characteristics of crumble ration. The treatmentswere commercial ration (basal ration) + 2% tapioca, basal ration + 2% bentonite and basal ration + 2% onggok. The parameters observed were water content, water activity, particle size, specific density, bulk density,compact bulk density, angle of heap, softness and impact resistance of crumble and durability. The experimental data were analysed using analysis of variance according to completely randomised design consisted of four treatments and five replications for each treatment and the differences among treatments were further tested using Duncan Multiple Range Test. The result of this experiment showed that the addition oftapioca, bentonite and onggok as binders affected(P<0.01) physical chracteristics of crumble. It affected  water content, water activity, bulk density, compactbulk density and durability. Particle size of ration with binders was significantly different from commercial ration. Ration with tapioca binder had the lowest value for water content and water activity, i.e. 9.42% and 0.84 respectively. Ration with bentonite binder had the highest value for bulk density, compacted bulk density, and durability, i.e. 0.686 g/cm3, 0.769 g/cm3, and 95%, respectively. Particlesize of ration which was binded with tapioca, bentoniteor onggok was categorised moderate compared to the commercial one.